MCSA guide to installing and configuring Microsoft Windows Server 2012/R2, exam 70-410 - Tomsho, Greg (Networking (Course Technology, Inc.), 2015)
Packed with hands-on applications, this book empowers students to pass the MCSE/MCSA certification exam while preparing them to successfully meet the real-world challenges of a Microsoft networking professional